PENGARUH CLAPPING, VIBRASI DAN SUCTION TERHADAP TIDAL VOLUME PADA PASIEN PNEUMONIA YANG MENGGUNAKAN VENTILATOR DI RUANG ICU ROYAL PRIMA MEDAN - Agnesia Vaulina; Yana Malinda; Yunistia Gulo; Victory Oktavianus; Tiarnida Nababan (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2019)
See the impact that can occur in patients who use ventilators and the ability of patients to issue very limited secretions, it is very necessary to help the patient in maintaining the hygiene of the road, so that the breathing runs smoothly. One of the efforts that can be done is clapping, vibration and suction in accordance with the operational standards of Prosdur. The purpose of this research is to identify the influence of clapping, vibration and suction against tidal volumes in pneumonia patients who use a ventilator in the ICU room of Royal Prima Medan Hospital. The design of this research uses the experimental quasi method. Samples on this study were as much as 10 people based on the total population during 2 weeks from 1st to 15th July 2019 with total sampling technique. The instrument used is an observation sheet in a ventilator-using pneumonia patient. The test used in this study is the T-Dependen test to see the influence of clapping, vibration and suction against tidal volumes with significant value (P < 0.05). The advice of this research is to be expected to the hospital, especially health workers pay attention to the hygiene of the airway by doing the action of claping, vibration and suction especially in patients who are diagnosed with pneumonia are treated with ventilators.